Is this the end of the Job Network model? The evolution and future of performance‐based contracting of employment services in Australia. Issue 3 (13th February 2022) - Davidson, Peter
Abstract: Australia was the first OECD nation to privatise its public employment service, replacing it with the "Job Network model" of performance‐based contracting. A "New Employment Services Model" commences in July 2022 following a major review. To assess the prospects for systemic reform, we trace the model's development from 2007–2019 in response to changes of government and policy goals, tensions within the model and labour market conditions. One reason for the model's endurance is that it met the policy goal of successive governments to closely supervise job search at low cost. The Job Network was poorly suited to the policy shift under Labor governments (2007–2013) towards skills development, but they found it less fiscally and politically costly to layer new programs on top than transform the model. Its poor performance in reducing long‐term unemployment and declining take‐up by employers triggered the recent review, which recommended the transfer of those closest to employment to an online service, a licensing system, and less reliance on outcome payments. The review's proposals could lead to systemic change, but only if underpinned by a shift in policy goals from benefit compliance and cost containment towards greater agency for, and investment in, unemployed people.